Analysis of spontaneous reports of suspected adverse reactions after vaccination against COVID-19 in Slovakia - Lassanova, Monika; Lassan, Stefan; Liskova, Silvia; Tesar, Tomas; Cicova, Monika (Frontiers in Pharmacology, 2023)
Introduction: The COVID-19 pandemic has resulted in more than 6.5 million deaths worldwide yet. Vaccination against the SARS-CoV-2 virus is a reliable way out of the pandemic, however, vaccination rate reaches only 58% in the Slovak Republic. Concerns about the adverse reactions of vaccines are one of the reasons for the low vaccination rate. Objective: The aim of our analysis was to review reported suspicions of adverse reactions (ARs) of registered COVID-19 vaccines (Comirnaty, Vaxzevria, Spikevax), which State Institute for Drug Control received from healthcare professionals and patients in the period from 1 January 2021 to 31 May 2021. Methods: Data were collected from the State Institute for Drug Control database, a retrospective analysis was carried out focusing on trends in the number of all reports of suspicions of adverse reactions sent to the State Institute for Drug Control during the previously mentioned period. We analysed the Retrieved data were analysed with the usage of descriptive statistics and comparison to historical data on drug adverse reactions in Slovakia was performed. Results: During the evaluation period, 5,763 reported suspicions of adverse reactions were analysed, overall, there was a significant (p < 0.0001) increase in the number of reported adverse reactions fivefold. 93% of ARs (n = 5,346) were reported for COVID-19 vaccines. In comparison of the extentof all adverse reactions, there is clearly a statistically significant difference between all types of vaccines administered at that time (p ≤ 0.0001). No statistically significant difference (p ≤ 0.238) was identified between Spikevax and Comirnaty in the proportion of serious adverse reactions. However, a significantly higher (p ≤ 0.00001) proportion of reported suspicions of serious adverse reactions was observed after the administration of Vaxzevria. Conclusion: This is the first analysis conducted in Slovakia aimed to reported adverse reactions in relation to the administration of COVID-19 vaccines. The rate of spontaneously reported suspected adverse reactions has been insufficient in the past for a long time; during the period from January to May 2021 the reporting rate increased due active calls for adverse reactions reporting. In concordance with European data, Vaxzevria had a significantly higher ratio of reported suspicions of serious adverse reactions.